The relevance of household contacts tracing among child contacts of patients with multidrug-resistant tuberculosis - Raznatovska, O. M.; Moskaliuk, A. S.; Grekova, T. A.; Chernyshova, L. I.; Pushnova, O. O.; Shelesti, T. I.; Разнатовська, Олена Миколаївна; Москалюк, А. С.; Грекова, Тетяна Анатоліївна; Чернишова, Л. І.; Пушнова, О. О.; Шелестіна, Т. І. (My University, 2020)
BACKGROUND. The World Health Organization (WHO) reports an unknown contact history of pediatric tuberculosis (TB), especially in children younger than 5 years old. Tracing pediatric household contacts of patients with multidrug-resistant TB (MDR-TB) is considered to be a highly effective intervention for detection of new cases of chemoresistant TB in children and timely prevention of its transmission. OBJECTIVE. To study the nature of TB process manifestations and concordance of mycobacterium tuberculosis (MBT) drug resistance profiles in household child contacts of patients with MDR-TB. MATERIALS AND METHODS. The nature of TB process manifestations and concordance of MBT drug resistance profiles in 12 household child contacts of patients with MDR-TB in 6 households (6 adult MDR-TB index patients, IP) were studied. Adults and children were examined and treated in the Pulmonary Tuberculosis Department No 3 and in the Pediatric Department of the Clinical Base of the Department of Phthisiology and Pulmonology of Zaporizhzhia State Medical University at the Municipal Institution “Zaporizhzhia Regional Tuberculosis Clinical Dispensary”. RESULTS AND DISCUSSION. The tracing of children who were household contacts of the MDR-TB IP revealed the following features. The incidence of child TB was 2 times higher than that of contact adults (44 % vs. 20 %). Moreover, the incidence among children younger than 2 years of age was almost 3 times higher than in children across other age groups (54.5 % vs. 18.2 % in children younger than 5 years of age and 18.2 % in children aged 5 years and older). The children were non-BCG vaccinated in 63.6 % of cases. There was an alarmingly high rate of non-BCG vaccinated children, namely 83.3 % among individuals younger than 2 years of age and all of those younger than 5 years of age (100 %). The children mostly presented small clinical forms of non-destructive TB: intrathoracic lymph node TB (36.4 %), MBT complex (36.4 %) and focal TB (18.2 %). Most of the children (63.6 %) who developed TB were detected within the first year of IP with MDR-TB follow-up, and it is worthy of note that in the majority of cases (4 households; 66.6 %). With respect to the concordance of MBT drug resistance profiles between the children and MDR-TB IP in the households, diagnosis in children was microbiologically confirmed in only 3 cases (3 households) demonstrating the complete concordance of profiles in each one. At the same time, the complete concordance of MBT drug resistance profiles between adult household contacts and the MDR-TB IP was also recorded in 3 cases. As is evident, across the household contacts group aged between 0 and 18 years who were exposed to the MDR-TB IP, the most susceptible to develop TB were non-BCG vaccinated children younger than 2 years. More worryingly is that among 3 microbiologically conformed individuals of this age group, 2 children younger than 2 years were found to have their own drug resistant MTB isolates. CONCLUSIONS. Tracing household child contacts of MDR-TB IP is particularly effective for timely detection of active TB within the first year of MDR-TB IP follow-up. Non-BCG vaccinated children younger than 2 years of age are at the highest risk for MDR-TB followed by non-BCG vaccinated children younger than 5 years of age. The early detection and timely antimycobacterial therapy initiation based on drug susceptibility test results of a MDR-TB IP is a guarantee not only for an effective treatment but also for a reduction in the MDR-TB transmission to other persons. ОБҐРУНТУВАННЯ. Експерти Всесвітньої організації охорони здоров’я (ВООЗ) вказують, що захворювання на туберкульоз (ТБ) у дитячому віці, особливо до 5 років, свідчить про невстановлене джерело інфекції. Відстеження дітей, які контактували з хворими на мультирезистентний ТБ (МРТБ) у межах домогосподарства, є високоефективним втручанням для своєчасного виявлення нових випадків хіміорезистентного ТБ у дітей і запобігання його передачі. МЕТА. Вивчення характеру проявів туберкульозного процесу та збігу профілів лікарської стійкості мікобактерій туберкульозу (МБТ) у дітей, які контактували з хворими на МРТБ у межах домогосподарства. МАТЕРІАЛИ ТА МЕТОДИ. Характер проявів туберкульозного процесу та збіг профілів лікарської стійкості МБТ вивчалися в 12 дітей, які контактували з хворими на МРТБ у межах 6 домогосподарств (6 дорослих індексних пацієнтів (ІП) з МРТБ). Обстеження та стаціонарне лікування дорослих і дітей відбувалися у відділенні легеневого туберкульозу № 3 та в дитячому відділенні клінічної бази кафедри фтизіатрії і пульмонології Запорізького державного медичного університету в Комунальній установі «Запорізький обласний протитуберкульозний клінічний диспансер». РЕЗУЛЬТАТИ ТА ЇХ ОБГОВОРЕННЯ. Відстеження дітей, які контактували з ІП з МРТБ у межах домогосподарства, дало змогу виявити такі особливості. Дитяча захворюваність на ТБ у 2 рази перевищувала таку в контактних дорослих (44 % проти 20 %). При цьому захворюваність серед дітей віком до 2 років була вищою майже в 3 рази щодо інших розрізів дитячого віку (54,5 % проти 18,2 % у віці до 5 років і 18,2 % у віці понад 5 років). У 63,6 % випадків діти не були щеплені вакциною БЦЖ. Насторожує той факт, що нещепленими були 83,3 % дітей до 2 років і всі діти до 5 років (100 %). Серед клінічних форм захворювання в дітей переважали малі форми недеструктивного ТБ: ТБ внутрішньогрудних лімфатичних вузлів (36,4 %), первинний туберкульозний комплекс (36,4 %) і вогнищевий ТБ (18,2 %). Більшість дітей (63,6 %), які захворіли на ТБ, виявлені в перший рік спостереження за ІП з МРТБ, при цьому в переважній кількості домогосподарств – 4 (66,6 %). Щодо збігу профілів лікарської стійкості МБТ у домогосподарствах у дітей з ІП з МРТБ, то бактеріовиділення зареєстровано лише в 3 дітей (3 домогосподарства) й у всіх випадках встановлено повний збіг профілів. При цьому в 3 домогосподарствах у дорослих контактних осіб зареєстровано також повний збіг профілів лікарської стійкості МБТ з ІП з МРТБ. Отже, серед контингенту віком 0-18 років, які контактували з ІП з МРТБ у межах домогосподарства, найбільш схильними до розвитку ТБ були невакциновані діти до 2 років. Викликає занепокоєння те, що серед 3 бактеріовиділювачів цього контингенту власна лікарська стійкість МБТ була діагностована у 2 дітей віком до 2 років. ВИСНОВКИ. Відстеження дітей, які контактували з ІП з МРТБ у межах домогосподарства, є особливо корисним для своєчасного виявлення в них активного ТБ у перший рік спостереження за ІП з МРТБ. Найбільшою групою ризику МРТБ є не щеплені вакциною БЦЖ діти до 2 років, на другому місці – не щеплені вакциною БЦЖ діти до 5 років. Раннє виявлення та своєчасне призначення антимікобактеріальної терапії з урахуванням результатів тесту на медикаментозну чутливість ІП з МРТБ є запорукою не лише ефективного лікування, але й скорочення подальшої передачі МРТБ.
Актуальність відстеження дітей, які контактували з хворими на мультирезистентний туберкульоз у межах домогосподарства
Keywords: contact tracing; household; children; multidrug-resistant tuberculosis; відстеження контакту; домогосподарства; діти; мультирезистентний туберкульоз